Pengaruh Pelatihan, Pengembangan Karir dan Produktivitas Kerja Terhadap Kualitas Pelayanan Karyawan The Arista Hotel Palembang - Ahmad Muhammad Ridho (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
Theese study aims to determine the effect of Training, Career development and Work Productivity against quality of service employees the Arista Hotel Palembang. In this study the number of population is 120 people, 50 % of samples taken from a population that is 60 people with the details of 20 people as test sample and a sample of 40 people. Sampling in this study using the technique of saturated samples. From these results is significant effect of training, Career development and work productivity simultaneously to quality services employees the Arista Hotel Palembang. With the regression model Y = 3.502 + 0.360X1 + 0.254X2 + 0.453X3 + e. All three independent variables go hand in hand with the dependet variable means higher the quality of services employees the Arista Hotel Palembang. There is a significant effect partially on quality training services employee of the Arista Hotel Palembang, indicated sig t of 0.035 < α ( 0.05 ). There is significant effect of career development partilay on quality services employees the Arista Hotel Palembang, indicated sig t of 0.009 > α (0.05). There is significant effect partially on work productivity employee service quality the Arista Hotel Palembang. Indicated sig t off 0.009 > α (0.05), work productivity variable has a more dominant effect of 45.3%. Implementation is an effort to improve training, such behavior (psychomotor, affective and cognitive), tingkatan (primary and secondary) and content (Instructor, teaching materials and activities of the participants). Efforts to improve career development, such as the ability to complete the work, and to characterize changes in behavior/attitude. Efforts to improve the productivity of work, such a experience, ability, ways working, skill in the work, the results achieved, the level of error and the Volume of work.